2012
DOI: 10.1172/jci64750
|View full text |Cite
|
Sign up to set email alerts
|

Convergence of oncogenic and hormone receptor pathways promotes metastatic phenotypes

Abstract: Cyclin D1b is a splice variant of the cell cycle regulator cyclin D1 and is known to harbor divergent and highly oncogenic functions in human cancer. While cyclin D1b is induced during disease progression in many cancer types, the mechanisms underlying cyclin D1b function remain poorly understood. Herein, cell and human tumor xenograft models of prostate cancer were utilized to resolve the downstream pathways that are required for the protumorigenic functions of cyclin D1b. Specifically, cyclin D1b was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 65 publications
1
54
1
Order By: Relevance
“…Notably, Slug has been well documented to be involved in the induction of epithelial-mesenchymal transition in a variety of cancers, including the prostate (Medici et al 2008, Emadi Baygi et al 2010. Indeed, Augello et al (2013) observed that knockdown of SNAI2 by siRNA significantly suppressed the invasive capacity of prostate cancer cells. In addition, this effect was more pronounced in cells that over-expressed cyclin D1b (Augello et al 2013).…”
Section: Rewiring Of Ar Signaling Axis By Cyclin D1bmentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, Slug has been well documented to be involved in the induction of epithelial-mesenchymal transition in a variety of cancers, including the prostate (Medici et al 2008, Emadi Baygi et al 2010. Indeed, Augello et al (2013) observed that knockdown of SNAI2 by siRNA significantly suppressed the invasive capacity of prostate cancer cells. In addition, this effect was more pronounced in cells that over-expressed cyclin D1b (Augello et al 2013).…”
Section: Rewiring Of Ar Signaling Axis By Cyclin D1bmentioning
confidence: 99%
“…To further delineate the mechanisms that underpin the pro-tumorigenic activity of cyclin D1b in prostate cancer, Augello et al (2013) carried out microarray and gene ontology analyses to identify and characterize genes uniquely regulated by cyclin D1b. They found that a number of these cyclin D1b-regulated genes are functionally associated with altered cell migration, invasion, and differentiation.…”
Section: Rewiring Of Ar Signaling Axis By Cyclin D1bmentioning
confidence: 99%
See 3 more Smart Citations